2012
DOI: 10.1364/oe.20.025432
|View full text |Cite
|
Sign up to set email alerts
|

High-speed terahertz reflection three-dimensional imaging for nondestructive evaluation

Abstract: We demonstrate high-speed terahertz (THz) reflection three-dimensional (3D) imaging based on electronically controlled optical sampling (ECOPS). ECOPS enables scanning of an axial range of 9 mm in free space at 1 kHz. It takes 80 s to scan a transverse range of 100 mm × 100 mm along a zigzag trajectory that consists of 200 lines using translation stages. To show applicability of the imaging system to nondestructive evaluation, a THz reflection 3D image of an artificially made sample is obtained, which is made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Many polymers are transparent to the wavelengths of 30 μm to 3 mm corresponding to the 0.1 to 10 THz range (200). Thus, terahertz testing can be applied in transmission or reflection as well as in scanning or imaging mode (201)(202)(203)(204). It has been applied to aircraft components (205), impact damage characterization (206), damage detection (207), fiber orientation (208), thickness measurement by terahertz pulsed imaging (209), and surface profiling by phase sensitive terahertz holography (210)…”
Section: Electromagnetic Test Methodsmentioning
confidence: 99%
“…Many polymers are transparent to the wavelengths of 30 μm to 3 mm corresponding to the 0.1 to 10 THz range (200). Thus, terahertz testing can be applied in transmission or reflection as well as in scanning or imaging mode (201)(202)(203)(204). It has been applied to aircraft components (205), impact damage characterization (206), damage detection (207), fiber orientation (208), thickness measurement by terahertz pulsed imaging (209), and surface profiling by phase sensitive terahertz holography (210)…”
Section: Electromagnetic Test Methodsmentioning
confidence: 99%
“…spinning or vibrating mirror devices) can produce several hundreds of picoseconds of delay range with a high scanning rate typically more than few hundreds of hertz. Recently, very promising results were published about the design of compact and inexpensive terahertz imaging systems relying on femtosecond fiber laser technology without mechanical stage (Ecops [68], Asops [69], OSCAT [70]). In these cases, the motion of the scanning delay line must be synchronized to the raster scan of the object, so that it is possible to determine the location of the object at the moment each waveform is acquired.…”
Section: Time Domain Techniquesmentioning
confidence: 99%
“…Recently, many researchers reported that several polymer materials feature very low absorption and refractive index in the THz region (11,21). Thus, THz technology appears to be useful for characterizing dielectric material properties (23), superstructures (13), voids (22,31,41), inclusions (22,42), defects (22,25,27), glass transition (43), and material aging processes (11). Moreover, the wavelength of THz radiation is comparable to foam cell size (14,21) and additives or fillers (22,23).…”
Section: Plastic and Foam Polymer Materialsmentioning
confidence: 99%
“…Recently, new designs of nearly alignment-free THz systems without any mechanical delay line were introduced: optical sampling by cavity tuning (78), asynhronous optical sampling (79), and electronically controlled optical sampling (80). The last has already been applied for the reflection 3D imaging of defects in composite materials (42). Hence, the majority of research work is focused on the development of high-speed, highresolution, and high-power sources based on graphene, metamaterials, quantum cascade lasers, plasmonic photoconductive emitters, and THz detector arrays.…”
Section: Advantages and Limitations Of Thz Spectroscopy And Imagingmentioning
confidence: 99%